Investigation on Control Strategies for a Single-Phase Photovoltaic Inverter Using PSCAD/EMTDC Software - Henz Cristiano Luiz (Sciendo, 2021)
In the last decades, electric power produced through photovoltaic conversion has been increasing because of the need to reduce fossil fuel burning. Recently, photovoltaic systems have become more competitive and their role in the renewable energies market share is steadily gaining in importance. Improvements in the power electronics employed in the DC/AC conversion are topics of interest in the quest for more efficient and eventually reduced-cost inverters. The goal of this paper is to perform an investigation of control strategies and propose a topology for a single-phase DC/AC converter for photovoltaic arrays using the simulation software Power System Computer Aided Design/ Electromagnetic Transient Design and Control (PSCAD/EMTDC). The circuit proposed in this paper employs an isolating transformer to a grid-connected photovoltaic inverter. The control strategy proposed uses the instantaneous reactive power theory (p–q theory) and phase-locked loop (PLL). The p-q theory uses two virtual axes in the Park Transformation, which provide to the control system a good dynamic response, accuracy, and decoupling between the control and power system. Computer simulations using the electromagnetic transient software PSCAD show the efficiency of the proposed strategy for a single-phase inverter. The control strategy and topology are quite simple and easy to implement in the future using a Digital Signal Processor (DSP). The results provide insights into new power electronics solutions, which can improve the efficiency and efficacy of the current available in DC/AC converters for photovoltaic systems.